Sustainability Contextualized in Malaysia - Long, Alwin; Tazilan, Azimin; Halim, Sharina (International Journal of Engineering and Technology, 2018)
Achieving sustainability has been the ultimate goal for many individuals, communities and nations. Yet all these stakeholders represent micro to macro level of the global community. Progression to decipher sustainability differs from macro all the way down to micro level. The overview on sustainability helps draw the spectrum of evaluation diversity. Many initiatives failed due to unmatched needs. Some of the initiatives that are successful are mainly biased towards a spectrum of the holistic sustainability needs. Intention of the paper is to publish the life cycle of ASEAN Energy Management Scheme (AEMAS) a macro strategy implemented through the micro level of deployment, complete with appraisal. Amongst its ASEAN peers, Malaysia championed the AEMAS program as essential micro building block towards the larger agenda of a low carbon city.Â  The top down approach employing strategic government ministries and local policies drive the intention into reality making the 15th Session Conference of the Parties (COP15) commitment highly achievable. This analysis precedes both AEMAS and COP15 towards larger peripheries of LCC and COP21. The result will benefit all stakeholders such as the general public, academicians, government and policy makers who are working on sustainability topics.Â